Experimental Study of the Pore Structure Deterioration of Sandstones under Freeze-Thaw Cycles and Chemical Erosion - Jielin Li; Rennie B. Kaunda; Longyin Zhu; Keping Zhou; Feng Gao (Advances in Civil Engineering)
The issue of rock deterioration in chemical environments has drawn much attention in recent years in the rock engineering community. In this study, a series of 30 freeze-thaw cycling tests are conducted on sandstone samples soaked in H2SO4 solution and in pure water, prior to the application of nuclear magnetic resonance (NMR) on the rock specimens. The porosity of the sandstone, the distribution of transverse relaxation time T2, and the NMR images are acquired after each freeze-thaw cycle. The pore size distribution curves of the sandstone after freeze-thaw cycles, four categories of pore scale, and the features of freeze-thaw deterioration for pores of different sizes in H2SO4 solution and pure water are established. The result shows that, with the influence of the acid environment and the freeze-thaw cycles, the mass of the samples largely deteriorates. As the freeze-thaw cycles increase, the porosity of rocks increases approximately linearly. The distribution of the NMR T2 develops gradually from 4 peaks to 5 or even to 6. Magnetic resonance imaging (MRI) dynamically displays the process of the freeze-thaw deterioration of the microstructure inside the sandstones under acid conditions. The results also show pore expansion in rocks under the coupling effects of chemistry and the freeze-thaw cycles, which differ largely from the freeze-thaw deterioration of the rock specimens placed in pure water.